Comparison of Respiratory and. Hemodynamic Parameters of COVID-19 and Non-COVID-19 ARDS Patients - (:unkn) unknown (JAYPEE BROTHERS MEDICAL PUBLISHERS PVT LTD, 2021)
Background: COVID-19 can cause a clinical spectrum from asymptomatic disease to life-threatening respiratory failure and acute respiratory distress syndrome (ARDS).There is an ongoing discussion whether the clinical presentation and ventilatory parameters are the same as typical ARDS or not.There is no clear understanding of how the hemodynamic parameters have been affected in COVID-19 ARDS patients. We aimed to compare hemodynamic and respiratory parameters of moderate and severe COVID-19 and non-COVID-19 ARDS patients.These patients were monitored with an advanced hemodynamic measurement system by the transpulmonary thermodilution method in prone and supine positions. Patients and methods: Data of 17 patients diagnosed with COVID-19 and 16 patients diagnosed with other types of diseases with moderate and severe ARDS, mechanically ventilated, placed in a prone position, had advanced hemodynamic measurements with PICCO, and stayed in the intensive care unit for more than a week were analyzed retrospectively. Patient characteristics and arterial blood gases analysis recorded at admission and respiratory and advanced hemodynamic parameters during the first week were compared in prone and supine positions. Results: No difference was observed in the respiratory parameters including respiratory system compliance between COVID-19 and non-COVD-19 patients in prone and supine positions. In comparison of advanced hemodynamic parameters in the first week of intensive care, the extravascular lung water and pulmonary vascular permeability indexes measured in supine position of COVID-19 ARDS patients were found to be significantly higher than non-COVID-19 patients. Duration of prone position was significantly longer in patients diagnosed with COVID-19 ARDS. Conclusions: The results of this study suggested that COVID-19 ARDS is a variant of typical ARDS with a different pathophysiology.
Keywords: ARDS patients; COVID-19; Hemodynamic parameters; Transpulmonary thermodilution method